Pd-Catalyzed Carbonylative Conjugate Addition of Dialkylzinc Reagents to Unsaturated Carbonyls - Custar, Daniel W. (2010)
[Image: see text] The Pd-catalyzed addition of organozinc reagents to unsaturated carbonyls in the presence of carbon monoxide provides 1,4-diketones in good yield. The reaction was studied with a number of substituted cyclic and acyclic ketones as well as α,β-unsaturated aldehydes.